"ḵẖus̲ẖub musannadah" (Qurʾān 63.4) and Epigraphic South Arabian ms³nd - Elmaz, Orhan (Proceedings of the Seminar for Arabian Studies, 2011)
This paper will enquire into the possibility of a relationship between musannadah in Qurʾān 63. 4 and musnad (Epigraphic South Arabian (ESA) ms³nd), which is used to denote Epigraphic Arabic scripts and inscriptions. The question to be dealt with here is whether and how different interpretations evolved. In addition, the paper considers whether musannadah can be interpreted in the light of Epigraphic South Arabian ms³nd — and, subsequently, Arabic musnad denoting Ancient Arabian scripts — or, more specifically, the Ancient South Arabian monumental script. This would constitute a new interpretation and show the hypocrites to be corroded by fear like carved or rotten timbers; therefore lexicographical and exegetical as well as relevant secondary literature will be surveyed diachronically. The discussion will include proposed etymologies for the term musnad and its description in early Arabic sources such as Hamdānī’s Iklīl, the Gh͟arīb literature, Ḥadīth͟ collections, and historical works such as Jawād ʿAlī’s al-Mufassalfi tārīkh͟ al-ʿarab qabl al-islām.